Stanowisko paryskiej „Kultury” wobec europejskich procesów zjednoczeniowych w latach 1947–1957 - Barabasz, Adam (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
The paper deals with the analysis of the attitudes presented on the pages of the Paris-based Kultura periodical, in the period of 1947–1957, towards the projects of European unification. After 1947, Polish émigré circles in Paris perceived the post-war projects to unite Europe as an opportunity to liberate Poland from the influence of the Soviet Union, and reconstruct Poland after the wartime demolition. At the same time, while these circles promoted the political unification of Europe, divided by the Iron Curtain since 1945, economic integration was of less interest to them. The objective of this paper is to present the universal nature of journalism in the Paris circles, which were mainly striving to politically integrate the whole of Europe, unlike the émigré circles in London, or the socialist authorities in Poland.